A Review: Monitoring Historical and Heritage Buildings Using Terrestrial Laser Scanning - Nasir, Nurhidayah; Nazirah Mohamad Abdullah; Nurmasitah Mohd Amran; Noor Azlin Harun; Azmal Sabil (Enhanced Knowledge in Sciences and Technology, 2024)
This study aims to investigate the effectiveness of using technology to conserve historic and heritage buildings, specifically the Sultan Ibrahim Jamek Mosque in Muar, Johor. The traditional method of conservation has been widely used, but it has limitations in terms of accuracy and efficiency. The study focuses on the use of Leica BLK360, a 3- Dimensional (3D) laser scanning, as a technology method for conservation. The scope of the study includes the comparison of the accuracy and efficiency of the Leica BLK360 with the traditional method, the identification of the benefits and challenges of using the technology, and the evaluation of the impact of the technology on the conservation process. The study will employ a mixed-methods approach, including site surveys, interviews, and observations, to collect data from experts in the field of conservation and stakeholders involved in the conservation of the Sultan Ibrahim Jamek Mosque. The findings of the study will contribute to the body of knowledge on the use of technology in conservation and provide insights for future conservation projects. The study is significant as it addresses the need for more accurate and efficient methods of conservation, especially for historic and heritage buildings that are of cultural and historical importance.